Seismic Characterization of Debris Flows: Insights into Energy Radiation and Implications for Warning. Issue 6 (14th June 2019) - Coviello, V.; Arattano, M.; Comiti, F.; Macconi, P.; Marchi, L.
Abstract: Debris flows represent a major hazard in mountainous areas, due to their rapid motion along steep channels and to the transport of large sediment volumes, including large boulders. In this paper, we present data of channelized debris flows characterized by different velocities and sediment concentrations recorded in an instrumented channel reach of the Gadria basin (eastern Italian Alps). From the analysis of the seismic energy produced by the interaction of solid particles with channel boundaries, we show that (i) the peak amplitudes are representative of the kinetic energy of each surge and (ii) most energy transfer occurs during the passage of the surge fronts. Then, we propose a debris flow detection algorithm based on the amplitude information gathered from a linear array of geophones installed along the channel. The short time average over long time average ratio of the seismic signal is used to early detect the debris flow occurrence in a continuous stream of seismic data. The algorithm recognizes moving, long‐lasting sources of ground vibration (i.e., debris flows) and filters out different seismic sources (i.e., anthropic noise, earthquakes, and rockfalls). The alarm is triggered when the short time average/long time average threshold is exceeded on two geophones, progressively with time from upstream to downstream. The algorithm is employed in the early warning system installed for research purposes at Gadria. Complementary data (rainfalls, flow stage measurements, and video recordings) permitted a detailed event characterization and alarm validation. During three monitoring seasons, all debris flows were successfully detected, with the alarm lasting for their entire duration, and no false positives were produced. Plain Language Summary: In mountain areas, rainstorms can trigger debris flows, which are mass movements intermediate between landslides and water floods that appear in form of waves with very steep fronts, often including large boulders. Debris flows can travel distances of kilometers at high velocity and represent a major hazard for infrastructures and human life. Therefore, the development of effective early warning systems for debris flows is a prime objective for scientists. Debris flows generate ground vibrations that can be recorded by geophones installed on the channel banks. We observed that the intensity of these ground vibrations is related to the kinetic energy of the debris flow, and we developed a novel warning algorithm for its detection. The algorithm recognizes moving, long‐lasting sources of ground vibration (i.e., debris flows) and filters out other seismic sources (i.e., anthropic noise, earthquakes, and rockfalls), detecting the arrival of the debris flow front about 1 min before it passes where the sensors are installed. A proper installation of the geophones upstream from a road or a railway can ensure a warning time of some minutes, which can be used for closing the transportation route and avoiding loss of lives. Key Points: The peak amplitude correlates with the kinetic energy of debris flows, and most energy transfer occurs during the passage of the surge fronts A debris flow warning algorithm based on the amplitude information gathered from a linear array of geophones is proposed At Gadria the algorithm detects all debris flow events; the alarm lasts for their entire duration, and no false positives are produced